Modeled Respiratory Tract Deposition of Aerosolized Oil Diluents Used in Δ9-THC-Based Electronic Cigarette Liquid Products - Ranpara, Anand; Stefaniak, Aleksandr B.; Williams, Kenneth; Fernandez, Elizabeth; LeBouf, Ryan F. (Frontiers in Public Health, 2021)
Electronic cigarette, or vaping, products (EVP) heat liquids (‘e-liquids’) that contain substances (licit or illicit) and deliver aerosolized particles into the lungs. Commercially available oils such as Vitamin-E-acetate (VEA), Vitamin E oil, coconut, and medium chain triglycerides (MCT) were often constituents of e-liquids associated with e-cigarette, or vaping, product use-associated lung injury (EVALI). The objective of this study was to evaluate mass-based physical characteristics of the aerosolized e-liquids prepared using these diluent-oils. These characteristics were particle size distributions for modeling regional respiratory deposition and puff-based total aerosol mass for estimating amount of particles delivered to respiratory tract. Four types of e-liquids were prepared by adding terpenes to diluent-oils individually: VEA, Vitamin E oil, coconut oil and MCT. A smoking machine was used to aerosolize each e-liquid at determined puff topography (volume of 55 milliliters for 3 seconds with 30 second intervals between puffs). A cascade impactor was used to collect size-segregated aerosol for calculating the mass median aerodynamic diameter (MMAD) and geometric standard deviation (GSD). The respiratory deposition of EVP aerosols on inhalation was estimated using the Multiple-Path Particle Dosimetry model. From these results, the exhaled fraction of EVP aerosols was calculated as a surrogate of secondhand exposure potential. The MMAD of VEA (0.61 micrometers (µm)) was statistically different compared to MCT (0.38 µm) and coconut oil (0.47 µm) but not to Vitamin E oil (0.58 µm); p < 0.05. A wider aerosol size distribution was observed for VEA (GSD 2.35) and MCT (GSD 2.08) compared with coconut oil (GSD 1.53) and Vitamin E oil (GSD 1.55). Irrespective of statistical differences between MMADs, dosimetry modeling resulted in similar regional and lobular deposition of particles for all e-liquids in the respiratory tract. The highest ( 0.08 or more) fractional deposition was predicted in the pulmonary region, which is consistent as the site of injury among EVALI cases. Secondhand exposure calculations indicated substantial of EVP aerosols could be exhaled, which has potential implications for bystanders. The number of EVALI cases has declined with removal of VEA; however, further research is required to investigate commonly available commercial ingredients used in e-liquid preparations.